Overcoming Barriers to Reform : On Incentive-Compatible International Assistance - Mayer, Wolfgang (IMF Working Papers; Working Paper ;, 2007)
International financial assistance (loans and grants) can potentially raise recipients' welfare in two ways, by affecting a direct resource transfer and by facilitating efficiency-enhancing reforms. In practice, barriers to reform limit the potential of assistance to deliver these two dividends. In this paper, we analyze assistance programs designed to ensure that recipient governments voluntarily adopt reforms and overcome barriers associated with: (i) the reaction of special interests to the prospect of reform; (ii) the possibility of default and political instability in the recipient country; and (iii) adverse selection and moral hazard. Reform barriers raise the cost of incentive-compatible assistance and may result either in no assistance being forthcoming or assistance that ensures repayment but not the implementation of reforms. Critical to the choice of assistance programs is the size of the rent accruing to special interests in the absence of reform and the limited liability rents needed to ensure that repayment terms do not threaten the country's political stability. Optimal assistance contracts feature flexible repayment terms related to real economic growth in recipient countries.